ARID1B/SUB1‐activated lncRNA HOXA‐AS2 drives the malignant behaviour of hepatoblastoma through regulation of HOXA3 - Liu, Gongbao (J Cell Mol Med, 2021)
It has been becoming increasingly evident that long non‐coding RNAs (lncRNAs) play important roles in various human cancers. However, the biological processes and clinical significance of most lncRNAs in hepatoblastoma (HB) remain unclear. In our previous study, genome‐wide analysis with a lncRNA microarray found that lncRNA HOXA‐AS2 was up‐regulated in HB. Stable transfected cell lines with HOXA‐AS2 knockdown or overexpression were constructed in HepG2 and Huh6 cells, respectively. Our data revealed knockdown of HOXA‐AS2 increased cell apoptosis and inhibited cell proliferation, migration and invasion in HB. Up‐regulation of HOXA‐AS2 promoted HB malignant biological behaviours. Mechanistic investigations indicated that HOXA‐AS2 was modulated by chromatin remodelling factor ARID1B and transcription co‐activator SUB1, thereby protecting HOXA3 from degradation. Therefore, HOXA‐AS2 positively regulates HOXA3, which might partly demonstrate the involvement of HOXA3 in HOXA‐AS2‐mediated HB carcinogenesis. In conclusion, HOXA‐AS2 is significantly overexpressed in HB and the ARID1B/HOXA‐AS2/HOXA3 axis plays a critical role in HB tumorigenesis and development. These results might provide a potential new target for HB diagnosis and therapy.